DESKRIPSI BAHAN AJAR MENULIS TEKS BIOGRAFI MENGGUNAKAN METODE ROLE PLAYING BERBANTUAN PREZI - Yola Argarani; Wikanengsih Wikanengsih; Mekar Ismayani (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The use of teaching materials during learning activities needs to be maximized so that the delivery of the material is more interesting and triggers the activeness of students in the class. Based on the results of online interviews and comparative analysis of two different theses, the produced special teaching materials using prezi with qualitative descriptive methods. From the results obtained, the analysis criteria include (1) material or content, (2) presentation of material, (3) suitability of material with student characteristics, (4) readability, and (5) language. The final product of this research is teaching material in the form of a guidebook of the preparation of teaching materials which contains four parts, namely (1) getting to know the prezi application, (2) the steps for making teaching materials using the prezi application, (3) writing biographical texts using the prezi application, and (4) Examples of teaching materials for writing biographical texts use the prezi application with the role playing method. The assessment of the feasibility of designing teaching materials was carried out by three judgement experts. Two lecturers of Indonesian Language and Literature Education at the IKIP Siliwangi and an Indonesian language subject teacher. The result of the combined validity is 94.73% with very valid category, it can be used but it needs a small revision. It is hoped that this research will make it easier for teachers to convey biographical text material for 10th grade students and be able to improve students' writing skills.